1980
DOI: 10.1002/1097-0142(19800801)46:3<547::aid-cncr2820460321>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal receptor determination in juvenile nasopharyngeal angiofibromas

Abstract: Juvenile nasopharyngeal angiofibromas (JNA) are rare. They have been frequently treated with estrogens, either solely or as an adjuvant therapy prior to surgery or irradiation. Clinical trials have proveded no evidence to explain the objective respose to estrogens observed in some tumors. Since the mechanism of steroid hormone action is mediated via specific receptors, we analyzed 8 JNA for tumor cytosol estrogen receptors. None were positive for estrogen receptors. Additionally, all were also negative for pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 20 publications
1
41
0
Order By: Relevance
“…These studies indicated that AR is frequently expressed at high levels in cases of JNA [18][19][20][21][22]. However, some studies indicated that ER and PR expression levels are high, while those of AR are low, in JNA [24,39,40].…”
Section: Literature Reviewsupporting
confidence: 93%
See 1 more Smart Citation
“…These studies indicated that AR is frequently expressed at high levels in cases of JNA [18][19][20][21][22]. However, some studies indicated that ER and PR expression levels are high, while those of AR are low, in JNA [24,39,40].…”
Section: Literature Reviewsupporting
confidence: 93%
“…JNA-related molecular studies have focused on sex hormone receptors, with investigations being done of androgen receptors (AR), estrogen receptors (ER), and progesterone receptors (PR) [6,10,14,[18][19][20][21][22][23][24]39,40]. These studies indicated that AR is frequently expressed at high levels in cases of JNA [18][19][20][21][22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies have aimed to demonstrate the role of androgen, estrogen and progesterone and particularly their nuclear receptors, for JNA behaviour, but so far the concept of hormone receptors remains controversial [43,45,46]. Current studies on the proliferation of stromal and vascular components of JNA have supported the hypothesis of the angiogenic growth factors playing a role in the pathogenesis [20,[46][47][48][49][50].…”
Section: Discussionmentioning
confidence: 97%
“…The correlation between the young age and the recurrence rate has been shown in numerous studies [15,36,41], and tumour growth has been considered to be related with the hormonal environment during male puberty [40,[42][43][44]. In the present series it was also noted that only one patient out of nine patients over 17 years old had a recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…This response may be due to anti-oestrogenic action of glucocorticoid [62]. Nasopharyngeal angiofibromas, occurring in boys around puberty, regress following oestrogen treatment [63]. During pregnancy arterial spiders may appear as well as palmar erythema [64], venectasies of legs, vulva and nailbed may already occur before increase of bloodvolume [65] and Raynaud's syndrome may ameliorate [64].…”
Section: Discussionmentioning
confidence: 99%